1989
DOI: 10.1016/0021-9991(89)90151-4
|View full text |Cite
|
Sign up to set email alerts
|

A second-order projection method for the incompressible navier-stokes equations

Abstract: In this paper we describe a second-order projection method for the time-dependent, incompressible Navier-Stokes equations. As in the original projection method developed by Chorin, we first solve diffusion-convection equations to predict intermediate velocities which are then projected onto the space of divergence-free vector fields. By introducing more coupling between the diffusion--{;onvection step and the projection step we obtain a temporal discretization that is second-order accurate. Our treatment of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
1,025
1
15

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,167 publications
(1,055 citation statements)
references
References 12 publications
14
1,025
1
15
Order By: Relevance
“…High-resolution methods were originally designed to address issues of accuracy, and physically-correct behaviour in the proximity of discontinuities such as shock waves, as well as contact discontinuities. ILES is the established numerical approach for compressible turbulent mixing but is also widely used in many other Bell and Colella (1989) and Drikakis et al (1994) have shown that non-oscillatory methods can also be used for incompressible flows. In this study, the incompressible and compressible Euler equations are solved by nonoscilatory methods (Drikakis and Rider 2004).…”
Section: Methodsmentioning
confidence: 99%
“…High-resolution methods were originally designed to address issues of accuracy, and physically-correct behaviour in the proximity of discontinuities such as shock waves, as well as contact discontinuities. ILES is the established numerical approach for compressible turbulent mixing but is also widely used in many other Bell and Colella (1989) and Drikakis et al (1994) have shown that non-oscillatory methods can also be used for incompressible flows. In this study, the incompressible and compressible Euler equations are solved by nonoscilatory methods (Drikakis and Rider 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Typically, the projection method only requires the boundary condition for velocity, and no boundary conditions for pressure are required. Actually, specifying the pressure boundary condition will overestimate the system (Bell et al, 1989). The pressure intrinsically satisfies the Neumann condition, which reads…”
Section: Projection Methodsmentioning
confidence: 99%
“…The Inlet and Wall cells are all interior to the domain, while the Outlet cells are situated on the domain boundaries, by extending the lumen of each vessel in its centerline direction [13] until it reaches the cartesian boundary. Our embedded boundary Navier-Stokes solver uses a fractional step method [14] that computes in a first step an intermediate velocity field, using the nonlinear advection-diffusion equation for velocity, and then projects the intermediate velocity onto the field of divergence free and tangent to the vessel boundary vector fields. For the velocity advection we use second-order upwind, Van-Leer slope limiting methods, while for the diffusion force components we use a semi-implicit approach as in [15] which is first order accurate and unconditionally stable in 3D.…”
Section: Patient-specific 3d Cfd Simulationsmentioning
confidence: 99%